Optimization of Real Time-Polymerase Chain Reaction (RT-PCR) Annealing Temperatures for the Detection of Superoxide Dismutase (SOD) in Wistar Rat (Rattus novergicus) Liver - Martati, Erryana; Kirana, Pramudhia Khansa; Mahatmanto, Tunjung (The Journal of Experimental Life Science, 2024)
Free radicals exposure causes oxidative stress in the human body and leads to various diseases, including cardiovascular, neurodegenerative disorders, cancer, diabetes, and aging. The endogenous enzymatic antioxidant superoxide dismutase (SOD) acts directly to reduce free radicals, and thus, its levels in tissue organs represent an important biomarker for oxidative stress in humans. One of the most reliable methods for detecting SOD is real-time polymerase chain reaction (RT-PCR). Still, the annealing temperatures and their results can vary widely depending on the samples. This study aims to optimize the annealing temperature of RT-PCR to detect SOD levels in liver tissue from Wistar rats (Rattus norvegicus). Total RNA was extracted from the liver tissue of one healthy Wistar rat using a cell lysis reagent. Purified RNA was reverse-transcribed into cDNA. The RT-PCR annealing temperature was optimized for detecting the expression of SOD with GAPDH (glyceraldehyde-3-phosphate dehydrogenase) as a reference housekeeping gene. The optimum RT-PCR annealing temperature for detecting SOD was 50°C, and GAPDH was 60°C. The optimization of annealing temperatures in RT-PCR is essential to obtain single peak readouts (higher specificity) and lowest Ct values possible (higher sensitivity). Keywords: Annealing temperature, Free radicals, RT-PCR, Superoxide dismutase, Wistar rat liver.